Sensory and consumer science as a valuable tool to the development of quinoa-based food products: More than three decades of scientific evidence. - Eduardo Palomino, Karina Erika (2024)
Solutions are needed to address both hunger and the promotion of healthy and sustainable diets. Quinoa, a nutritious and sustainable Andean grain, is a versatile option for creating new foods. Over the years, several technological advancements have been made to include quinoa in various food products. However, there is still a need for solid scientific evidence on the impact of quinoa on the product's acceptance. To address this scientific knowledge gap, this work aims to analyze the scientific literature over the last three decades regarding the sensory and hedonic impact of adding quinoa to food products. To do so, bibliometric methods based on the Scopus and Annual Scientific Production databases were used. After selecting and screening using the PRISMA method, seventy-four articles from 1991 to 2024 were analyzed, identifying relationships between keywords in the analyzed studies, forming a co-occurrence and co-authorship network. Results showed that quinoa has great nutritional potential when added to different food products, but its instrumental and sensory properties are modified. The nine-point hedonic scale was used to measure product acceptability in 47% of the articles. Studies on bakery products have shown that increasing the concentration of quinoa in the product formulation decreases the acceptance of the final product in 67% of cases. It is recommended to include consumer demands from a sensory and hedonic perspective when developing new products. The scientific and industrial community is encouraged to develop new food products catering to a broader consumer range. © 2024 Universidad Nacional de Trujillo. All rights reserved.